The role of body appreciation and boredom on married men’s sexual satisfaction - Josephine, Angelique Felicia; Sukamto, Monique Elizabeth; Redita, Natasya Engga (International Journal of Public Health Science (IJPHS), 2024)
Adult male appreciation of his body can affect sexual satisfaction. In addition, boredom caused by a lack of variety in sexual relations can also have an impact on sexual satisfaction in marriage. The aim of this study was to examine the role of body appreciation in predicting increased sexual satisfaction, either directly or indirectly through the mediation of sexual boredom, in early and middle-aged married men. Data were collected from a total of 382 participants (mean age 38 years) using a cross-sectional survey method with convenience sampling. Participants completed the extended satisfaction with life scale (ESWLS), body appreciation scale-2 (BAS-2), and sexual boredom scale (SBS). The results showed that sexual boredom partially mediated the indirect role of body appreciation in predicting sexual satisfaction (B=0.159; z=4.383; sig.=0.001<0.05) because body appreciation can also directly predict increased sexual satisfaction (B=0.814, t=11.418; sig.=0.001<0.05). This result indicates that body appreciation as an internal factor plays a greater role in predicting high sexual satisfaction in early and middle adulthood men.